2009
DOI: 10.1177/1527154409357795
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Framework for Understanding Interorganizational Relationships Between Nursing Homes and Emergency Departments: Examples From the Canadian Setting

Abstract: Nursing home residents who experience exacerbations of chronic health conditions or new illnesses must generally go to the emergency department for health care. This reliance on two distinct settings of care requires organizations to engage in an interorganizational relationship, which can be problematic, particularly when each organization has its own governing structures, policies, practices, and culture. Although it is widely acknowledged that interorganizational relationships can be the source of much frus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
1
6
0
7
Order By: Relevance
“…It is supported by previous research indicating that relationships between ED and RACF staff could be improved by providing information on each others' perspectives (McCloskey, Campo, Savage, & Mandville-Anstey, 2009). It is supported by previous research indicating that relationships between ED and RACF staff could be improved by providing information on each others' perspectives (McCloskey, Campo, Savage, & Mandville-Anstey, 2009).…”
Section: Communication Diffi Cultiessupporting
confidence: 67%
“…It is supported by previous research indicating that relationships between ED and RACF staff could be improved by providing information on each others' perspectives (McCloskey, Campo, Savage, & Mandville-Anstey, 2009). It is supported by previous research indicating that relationships between ED and RACF staff could be improved by providing information on each others' perspectives (McCloskey, Campo, Savage, & Mandville-Anstey, 2009).…”
Section: Communication Diffi Cultiessupporting
confidence: 67%
“…see [11,16,30]) and much of the literature is limited to one part of the system – the ED. Few focus on pre- and post-hospital transfer services.…”
Section: Discussionmentioning
confidence: 99%
“…While a number of US investigators have reported on transitions for NH residents, in particular NH-ED transitions [24-29], few Canadian studies exist that report on transitions for NH residents [30-32]. We do know that the in-hospital, and in particular ED experience for the frail NH resident is characterized by serious quality and safety concerns [33-36].…”
Section: Introductionmentioning
confidence: 99%